Development of “SITAYA” Interactive Multimedia (Solar System) to Stimulate Science Ability in Children Aged 5–6 Years - Hanisa Buabara; Syamsuardi Syamsuardi; Rika Kurnia R; Herlina Herlina (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
Early childhood science learning requires engaging and interactive media to support children’s curiosity and conceptual understanding, particularly for abstract topics such as the solar system. Interactive multimedia is considered an effective alternative to overcome limitations in conventional teaching methods for children aged 5–6 years. This study aimed to (1) describe the actual need for SITAYA (Solar System) interactive multimedia in stimulating science abilities in children aged 5–6 years, (2) determine the validity and practicality of the developed multimedia, and (3) examine its effectiveness in improving children’s science skills. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. Data were collected through observations and questionnaires. The research subjects involved four teachers and thirty children aged 5–6 years. Data analysis was conducted to assess validity, practicality, and effectiveness, as well as to test the research hypotheses. The results showed that SITAYA interactive multimedia was highly needed by teachers, as it was perceived as practical, attractive, and effective in stimulating children’s science abilities. Expert validation indicated that the multimedia met the valid criteria, while practicality assessment showed a very practical category. Effectiveness testing demonstrated that the multimedia was categorized as very effective. The findings revealed that the alternative hypothesis (H₁) was accepted and the null hypothesis (H₀) was rejected, indicating a significant effect of SITAYA interactive multimedia on the science abilities of children aged 5–6 years. Therefore, it is suggested that SITAYA interactive multimedia be integrated into early childhood science learning to enhance children’s understanding and engagement with scientific concepts.